Development banking in the Eastern Caribbean : the case of Saint Lucia and Grenada - Sandiford, Wayne (CEPAL SantiagoCL, 2007)
Examines the Saint Lucia Development Bank and the Grenada Development Bank. Looks at their origins as well as the emergence of development banking in these countries. Discusses the statutory basis of the development banks, their mandate, ownership and sources of funds. Looks at their structure and examines their governance and nature of government control.